Homens idosos avôs: significado dos netos para o cotidiano - Pedrosa, Aline da Silva (2006)
Masculine aging and grandparenthood are poorly studied themes. Geronthology presents itself as an instigative area for these thematics to be more explored. However, the presence of grandfathers in the educational and formative process of the grandchildren is a fact and refers us to a reorganization of the family nucleus. This research is intended to apprehend how the elderly interprets the grandfather-grandchild relationship, the exchange of experiences between generations, and the feelings which become evident on the daily routine. Considering that grandparenthood is a singular and personal phenomenon, by means of interviews this research was intended to gain some comprehension of meanings, values, and expressions. The research revealed that grandparenthood is associated to a strong feeling of parenthood. Grandfathers demonstrate great satisfaction in the relationship with their grandchildren